Economic and Trade Cooperation between Indonesia and Indochinese Countries - Pranata, Arueng Sy; Saputra, Junaidi; Seprina, Reka (Swarnadwipa, 2024)
Economic and trade cooperation between Indonesia and Indochinese countries (Vietnam, Laos, Cambodia, Myanmar and Thailand) has great potential to strengthen regional economic relations and encourage economic growth in Southeast Asia. As part of ASEAN, these countries seek to increase economic integration through various bilateral and multilateral agreements and cooperation. This article will answer the existing problem formulation regarding how Indonesia collaborates with Indochina in the existing economy and trade. The author also used library research in writing this article by collecting many sources through journals and other websites. With the conclusion, the author finds that economic and trade cooperation between Indonesia and Indochinese countries shows positive developments, but there are still many challenges that need to be overcome. Factors such as policy harmonization, infrastructure improvements, and institutional strengthening play an important role in increasing the effectiveness of this cooperation.